Current Siberian heating is unprecedented during the past seven millennia - Rashit M. Hantemirov; Christophe Corona; Sébastien Guillet; Stepan G. Shiyatov; Markus Stoffel; Timothy J. Osborn; Thomas M. Melvin; Ludmila A. Gorlanova; Vladimir V. Kukarskih; Alexander Y. Surkov; Georg von Arx; Patrick Fonti (Nature Communications, 2022)
A 7,638 yr summer temperature reconstruction based on subfossil trees buried in the Siberian Arctic shows that recent warming is unprecedented and interrupted a multi-millennial cooling trend.